Treinamento vocal para professores universitários: Uma revisão de escopo - Navarro, Leoni da Silva (2024)
The present work proposes to map the existence of vocal training strategies for university teachers, investigate vocal disorders present in the voice of Higher Education teachers and, if available, present descriptions of these disorders. It is based on the understanding that university professors can expose themselves to occupational risks, are subject to work overload, exacerbated productivity, little autonomy, stress, among others. Many pursue an academic career, but without knowledge about vocal care and this interferes with their quality of life and professional performance. The methodological proposal of the Joanna Briggs Institute was used. The searches took place in databases and digital libraries via the CAPES journal portal and were carried out in nine databases, between May and June 2023. The selection was carried out by two authors independently and a third author resolved the differences. 748 studies were identified. After applying the eligibility criteria, they were assessed whether or not they answered the research question; 10 primary studies were mapped, being national and international publications. As result of the mapping, vocal training strategies were found: brief and intensive therapy with the finger kazzo technique, manual perilaryngeal massage, traditional vocal training, preventive voice training programs, use of the resonance tube and speech therapy advice. The vocal disorders mentioned were: nodules on the vocal folds and behavioral dysphonia with symptoms of vocal fatigue and hoarseness due to muscle tension. It is possible to conclude that the identified vocal training contributed to improving the acoustic characteristics of the voice, improving emotion, well-being and vocal quality of teachers.